Our long marvelous dying - DeForest, Anna, 1986- (Little, Brown and Company, 2024)
"In a pandemic-hushed city, a young doctor lives a life of insecure attachments: to a distant partner in an untended marriage, to a loaner child who stirs up hurts from the past, to houseplants wilting in a dark apartment on a once-vibrant street. Through a yearlong fellowship caring for the dying and their families, death is impossible to ignore, and still more endings loom at every turn--endings made worse by wounded, avoidant doctors who don't know how to let go. But after the sudden loss of a long-estranged father, our unnamed narrator's work is thrown into painful relief, and we see, under threats large and small, how far we will go to hold on to our lives--no matter how little we live them"--